2001
DOI: 10.1093/emboj/20.21.5876
|View full text |Cite
|
Sign up to set email alerts
|

Identification of interaction domains of the prion protein with its 37-kDa/67-kDa laminin receptor

Abstract: IntroductionWe recently identi®ed the 37-kDa laminin receptor precursor (LRP) as an interactor for the prion protein (PrP) (Rieger et al., 1997; for reviews see Rieger et al., 1999;Gauczynski et al., 2001a). Employing a series of neuronal and non-neuronal cells, we proved that the 37-kDa LRP/67-kDa high-af®nity laminin receptor (LR) acts as the receptor for the cellular PrP (Gauczynski et al., 2001b). In the present manuscript we used the yeast twohybrid system and cell-binding studies on neuronal as well as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
224
0
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(234 citation statements)
references
References 41 publications
5
224
0
5
Order By: Relevance
“…By contrast, when the two dipeptides form part of the octarepeat units of different molecules, the inter-repeat site is intermolecular, as in Cu(II)⅐␣BoPrP-(24 -242) polymers formed using protein concentrations above 40 M (28). To envisage the interrepeat Cu(II) as a dimer of His-Gly dipeptides is also compatible with the observed retention of ␣PrP in a Cu(II)-loaded matrix (9,26) and the formation of a hetero-coordination complex with sulfated glycosaminoglycans and their assemblies (25,27).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…By contrast, when the two dipeptides form part of the octarepeat units of different molecules, the inter-repeat site is intermolecular, as in Cu(II)⅐␣BoPrP-(24 -242) polymers formed using protein concentrations above 40 M (28). To envisage the interrepeat Cu(II) as a dimer of His-Gly dipeptides is also compatible with the observed retention of ␣PrP in a Cu(II)-loaded matrix (9,26) and the formation of a hetero-coordination complex with sulfated glycosaminoglycans and their assemblies (25,27).…”
Section: Discussionmentioning
confidence: 86%
“…In the presence of Cu(II), PrP (as PrP C or ␣PrP) is retained in inner membrane immobilized metal ion affinity chromatography matrices, binds tighter to sulfated glycosaminoglycans and their complexes, and forms homo-polymers at protein concentrations above 40 M (9,(25)(26)(27)(28). Despite the large number of studies on Cu(II)-PrP interaction, the structural basis of the Cu(II)-mediated ␣PrP assembly and of the binding cooperativity are still unknown.…”
mentioning
confidence: 99%
“…1 A). At the N terminus, we found that HuM-E123, which recognizes the region of MoPrP (30)(31)(32)(33)(34)(35)(36)(37), bound weakly, and that HuM-E149, a HuM-Fab specific to the octarepeat region, bound even more weakly than HuM-E123 (Fig. 1 A).…”
Section: Immunochemical Characterization Of Wtmoprp-fc By Using Hum-fmentioning
confidence: 97%
“…These findings raise the possibility that the cells of the molecular layer express an auxiliary protein or proteins involved in prion formation, which is provisionally designated protein X and is likely to be distinct from a protein that may mediate Dpl-induced degeneration. The search for protein X has been frustrating because many proteins are known to bind to PrP C , but none have been shown to participate in PrP Sc formation (17,18,(28)(29)(30)(31)(32)(33)(34)(35)(36). Although the binding of the dominant-negative MoPrP(Q218K)-Fc to cells in the molecular layer where PrP C is expressed builds a case for the possibility that MoPrP-(Q218K)-Fc is binding to protein X, the absence of PrP Sc deposition in the molecular layer requires us to hypothesize that PrP Sc formed in molecular layer is readily transported to the cerebellar white matter where PrP Sc is found.…”
mentioning
confidence: 99%
“…Studies [34,92] have indicated that LR/ LRP may have a role in susceptibility to oral TSE infection, but there is no substantial evidence to suggest that they are surrogate markers of TSE diseases. Other studies have shown specific interactions between PrP and LRP [32,48]. Boehringer Ingelheim reports to have developed antibodies and oligonucleotides specific to the marker proteins and their mRNAs.…”
Section: Gamma Interferon and Prostaglandin E2mentioning
confidence: 99%